2011
DOI: 10.3928/01477447-20110526-11
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome Following Arthroscopic Fixation of Acromioclavicular Joint Disruption With the TightRope Device

Abstract: The objective of this study was to evaluate the preliminary radiographic and clinical results of grade IV and V acromioclavicular joint disruption repair using the arthroscopic Arthrex acromioclavicular TightRope (Naples, Florida) fixation technique. Numerous procedures have been described for surgical management of acromioclavicular joint disruption. The TightRope device involves an arthroscopic technique that allows nonrigid anatomic fixation of the acromioclavicular joint. A cohort of 10 men and 2 women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 39 publications
2
47
1
3
Order By: Relevance
“…The subjective improvement in all subjects seen in this study, regardless of reduction loss, has been reported by others [17].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The subjective improvement in all subjects seen in this study, regardless of reduction loss, has been reported by others [17].…”
Section: Discussionsupporting
confidence: 89%
“…Thiel et al [17] proposed using two TightRope devices (Arthrex, Naples, FL) to minimize reduction loss. This approach could potentially increase the risk of fracture; especially if biologic healing does not occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure could present as Lateral end clavicle osteolysis, hardware failure, or even fracture of coracoid or clavicle [16][17][18][19]. There have been reports of high failure of mechanical devices [20]. …”
Section: Bosworth Screwmentioning
confidence: 99%
“…While most injuries can be managed non-operatively, high-grade separations may result in persistent pain or functional decline and require surgical intervention [4][5][6][7][8][9]. Many surgical techniques have been described to stabilize the AC joint, however, the utility of many of these techniques are limited secondary to reported failure and complication rates [8,[10][11][12][13]. More recently, open or arthroscopically-assisted anatomic reconstruction of the coracoclavicular (CC) ligaments have been introduced and early follow-up appears encouraging [14][15][16].…”
Section: Introductionmentioning
confidence: 99%